ASIAN PUBLIC INTELLECTUALS’ ROLES IN COMBATTING TRAFFICKING IN ASEAN COUNTRIES - Rina Shahriyani Shahrullah (Fakultas Hukum Universitas Gadjah Mada, 2015)
The ASEAN Economic Community which facilitates free movement of people among ASEAN countries may cause a more progressive migration. One of the unintended consequences of migration is human trafficking. This paper suggests that there should be a collaborative measure taken by public intellectuals of ASEAN countries to combat human trafficking. Public intellectuals from receiving and sending countriesin ASEAN should share their information, knowledge, roles, responsibilities, resources, and services. This paper emphasizes that Asian public intellectuals as the member community in curbing human trafficking in the ASEAN region should involve government agencies, NGOs and communities. Masyarakat Ekonomi ASEAN yang menfasilitasi kebebasan penduduk negara anggota ASEAN untuk berpindah dapat menyebabkan terjadinya suatu migrasi besar-besaran. Salah satu konsekwensi yang tidak dikehendaki dari migrasi adalah perdagangan orang. Makalah ini menyarankan perlunya suatu langkah kerjasama yang dilakukan oleh intelektual publik di negara ASEAN untuk memerangi perdagangan orang. Intelektual publik dari negara penerima dan pengirim di ASEAN perlu untuk membagi informasi, pengetahuan, peranan, tanggung jawab, sumber daya, dan pelayanan mereka. Makalah ini menekankan bahwa intelektual publik Asia perlu melibatkan pemerintah, LSM and warga masyarakat.